1997
DOI: 10.1111/j.1745-4549.1997.tb00764.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effect of Allyl Isothiocyanate on Populations of Stored Grain Insect Pests

Abstract: The efficiency of the WasaOuro® system, based on an extract derived from Cruciferiae plants, was investigated as an insect suppressing agent. The active ingredient was allyl isothiocyanate (AIT). Lasioderma serricorne and Tribolium confusum were exposed to AIT vapor in vented containers. The containers were maintained in a temperature‐ and humidity‐controlled room. The WasaOuro system does not repel or attract L. serricorne but does reduce tunneling activity of T. confusum. AIT disrupts normal reproductive cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 3 publications
2
19
0
Order By: Relevance
“…Recently, the possibility of using AITC as a biological control agent has received a great deal of interest, studies being focused on the insecticidal, antibacteria and antifungi activities of AITC 23, 24. Worfel et al 25 tested the biological activity of AITC against Lasioderma serricorne (F.) and Tribolium confusum DuVal and found that AITC disrupted normal reproductive cycles of both species, resulting in a reduction in the population in grain.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the possibility of using AITC as a biological control agent has received a great deal of interest, studies being focused on the insecticidal, antibacteria and antifungi activities of AITC 23, 24. Worfel et al 25 tested the biological activity of AITC against Lasioderma serricorne (F.) and Tribolium confusum DuVal and found that AITC disrupted normal reproductive cycles of both species, resulting in a reduction in the population in grain.…”
Section: Introductionmentioning
confidence: 99%
“…Worfel et al (1997) also demonstrated the suppressive effects of mustard seed oil extract against insects that infest grain foods. Previous studies have demonstrated that the main antimicrobial factor in mustard seed oil extract is AIT (Clark, 1992).…”
Section: Introductionmentioning
confidence: 94%
“…Many studies have carried out to utilize allyl isothiocyanate as a fumigant, and it showed effectiveness when was applied to control coleopteran stored insect pests such as L. serricorne and T. confusum (Worfel et al, 1997), Ryzopertha dominica (Tsao et al, 2002), S. oryzae (Dilawari et al, 1991), and S. zeamais and L. entomophila (Wu et al, 2009). Besides insecticidal activity, allyl isothiocyanate is found to possess attractant effect to Delia brassicae (Wallbank & Wheatley, 1979), repellent effect against Culicoides impunctatus (Blackwell et al, 1997), and antimicrobial activity to infectious bacteria and fungi (Mayton et al, 1996;Delaquis & Sholberg, 1997).…”
Section: Fumigant Toxicity Of Horseradish Oil (C Armoracia)mentioning
confidence: 99%